2022
DOI: 10.1038/s41598-022-14629-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and prediction of tribological behaviour of filled polytetrafluoroethylene composites using Taguchi Deng and hybrid support vector regression models

Abstract: This study presents optimization and prediction of tribological behaviour of filled polytetrafluoroethylene (PTFE) composites using hybrid Taguchi and support vector regression (SVR) models. To achieve the optimization, Taguchi Deng was employed considering multiple responses and process parameters relevant to the tribological behaviour. Coefficient of friction (µ) and specific wear rate (Ks) were measured using pin-on-disc tribometer. In this study, load, grit size, distance and speed were the process paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…During training, the network updates these prior distributions based on the observed data, resulting in posterior distributions that reflect the updated beliefs about the weights. Instead of providing a single prediction, BRANNs can generate a distribution of predictions, [27][28][29] which represents the uncertainty associated with each prediction. This uncertainty estimation can be valuable in decision-making processes where knowing the confidence or reliability of the predictions is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…During training, the network updates these prior distributions based on the observed data, resulting in posterior distributions that reflect the updated beliefs about the weights. Instead of providing a single prediction, BRANNs can generate a distribution of predictions, [27][28][29] which represents the uncertainty associated with each prediction. This uncertainty estimation can be valuable in decision-making processes where knowing the confidence or reliability of the predictions is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers made similar observations. 11,40,42 Figure 11 shows the wear rates of PTFE, PA, and PP composites. Compared with PTFE, PTFE-Cu shows much better wear resistance.…”
Section: Wear Rates For Different Compositesmentioning
confidence: 99%
“…Thus, increased damage on the surface increases the coefficient of friction when sliding speed is high.When the contact pressure increases to 6 MPa, the friction behavior becomes unstable and coefficient of friction increase for PTFE (Figure6(a)). Some researchers have made similar observations40 while others reached opposite results 15. It is possible that an increasing applied load makes the contact interface closer, promoting transfer film formation, which result in more reduction in coefficient of friction.…”
mentioning
confidence: 91%
“…The evolutionary operation, factorial, regression, response surface, and Taguchi methods are the most used for experimental design [34][35][36] . Ibrahim et al 37 presented Taguchi optimization of tribological behaviors of composite materials. They concluded that Taguchi and analysis of variance (ANOVA) techniques are promising for predicting tribological behavior and can then be used to guide the design and implementation of tribological materials.…”
Section: List Of Symbolsmentioning
confidence: 99%